A low‐insert loss and high‐return loss bandpass filter based on cut‐off rectangular waveguide for satellite communication application. Issue 2 (1st August 2020) - Wu, Yong; Zeng, Qingsheng; Shang, Yuqiu
Abstract: This paper presents a low‐insert loss and high‐return loss bandpass filter (BPF). The proposed BPF consists of cut‐off rectangular waveguides and capacitive irises, showing an extremely low insert loss and a high return loss at 7.85‐8.5 GHz in the bandpass frequency range. The insert loss is less than 0.203 dB, the return loss is better than 30 dB and the attenuation exceeds 40 dB at 7.3 GHz and 9.05 GHz. Moreover, the fractional bandwidth of proposed BPF is 7.95%. The validity of the device was tested by comparison among experimental and simulation data; the results suggest that it is in satellite communication systems.